DEVELOPING A VIRTUAL LABORATORY FOR THE MATERIALS ON OPTICS TO INCREASE JUNIOR HIGH SCHOOL STUDENTS’ LEARNING OUTCOMES - Neni Yulianita; Tri Jalmo; Abdurrahman Abdurrahman (Universitas Negeri Yogyakarta, 2018)
This study aims to improve the concept mastery of students on optics through the development of a virtual laboratory. This research and development consisted of three stages, namely the preliminary study, the design of the virtual laboratory, and the virtual laboratory testing/implementation. The validity of the virtual laboratory is based on the results of the expert validation on the aspects of suitability of the contents and construction. The study used mixed-methods with exploratory sequential design in the form of Nonequivalent Control Group Design. The samples were taken using purposive sampling technique. This study involved 25 students of class VIII 1 as the experimental group and 25 students of class VIII 3 as the control group at Pugung Junior High School 1. The data were collected using observation, questionnaires and tests, and interviews. Then the data were analyzed using independent sample t-test and homogeneity test to see the learning effectiveness of the two sample groups. The results show that the practicality of learning using the developed virtual laboratory has been very successful and received good responses from the students. The effectiveness of the virtual laboratory can be seen from the N-gain of 0.44 (moderate level). Therefore, virtual laboratories can be used as teaching tools that are able to contribute positively to increase students’ learning outcomes.